2022
DOI: 10.4103/jehp.jehp_900_21
|View full text |Cite
|
Sign up to set email alerts
|

Study of medical students’ learning approaches and their association with academic performance and problem-solving styles

Abstract: BACKGROUND: Learners have various processing and understanding of the environment and issues and choose different strategies for problem-solving considering learning and studying approaches. The purpose of this study was to examine medical students’ learning approaches and their association with academic performance and problem-solving styles. MATERIALS AND METHODS: This study was conducted using the descriptive-correlational method. The statistical population comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This came in line with the findings of other studies [27,28]. Another study considered the development of the trainees' teaching methods to be one of the most important impacts of the FDPs [24].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This came in line with the findings of other studies [27,28]. Another study considered the development of the trainees' teaching methods to be one of the most important impacts of the FDPs [24].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the third level (behavior), the trained faculty gained the real benefits of training through application of their acquired new knowledge in their classes such as using sessions' ground rules, clarifying the learning objectives as well as engaging the students and checking their understanding. Likewise, another study revealed that classroom management and clearness of the objectives are considered among the features of a good teacher [24]. In addition, engaging the students helps the medical teachers to adequately understand the individual learning needs of the students and follow up their progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has been confirmed by numerous previous studies revealing that the demands of clinical training induce extreme levels of stress capable of negatively influencing academic and clinical performance as well as the psychological and physical health of students. [ 8 9 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Student status can also be a problem for patients or their families who do not want to deal with a student because of their lack of experience. [ 9 10 ] In addition, it would appear from student discourse that some clerkship settings are more stressful than others. Among them, emergencies and resuscitations due to the use of complex equipment or psychiatry due to the apprehension of the public are regularly mentioned.…”
Section: Introductionmentioning
confidence: 99%